Leiomyoadenomatoid tumor of uterus: two case reports with literature review - Flora Ávila Adorno; Karina Munhoz de Paula Alves Coelho; Giuliano Stefanello Bublitz; Jaqueline Stall; Paulo Henrique Condeixa de França (BMC, 2021)
Abstract Background Adenomatoid tumors (AT) are benign neoplasms of mesothelial origin that occur more frequently in the genital tracts. In uterus, AT are usually located in the subserosa of the cornual myometrium. Microscopically, it is characterized by interanastomosing pseudoglands or pseudovascular spaces and striking smooth-muscle hypertrophy is often present. In some cases, the prominence of smooth muscle component simulates a leiomyoma and the lesion is denoted as a leiomyoadenomatoid tumor. The microscopic appearance of the adenomatoid component (AC) may mimic a malignant tumor due to irregular pseudoinfiltration with tubular formations. Just 16 cases with this morphological presentation were found in the literature review. Case presentations The first case, a 38-year-old female, showed lower abdominal pain, menorrhagia, postcoital bleeding and previous history of uterin leiomyoma. The second case, a 26-year-old female, had clinical complaint of metrorrhagia and received diagnostic hypothesis of leiomyoma after ultrasound image. Both underwent myomectomy. Microscopically, the uterine masses showed intersecting smooth muscle bundles and gland like areas lined by cuboidal epithelioid cells that stained positive for WT1, D2-40 and calretinin in immunohistochemical analysis. Conclusions The cases were diagnosed as leiomyoadenomatoid tumor of the uterus. This is a benign and rare entity that may mimic malignant tumors due to the pseudo infiltrative appereance of the adenomatoid component, possibly leading to misdiagnosis.